ACCELERATION AND INNOVATION OF PRODUCTS MADE FROM LOCAL FOOD AT SMAN 1 BEBER, CIREBON REGENCY - Wiwit Estuti; Uun Kunaepah; Isnar Nurul Alfiyah (Jurnal Abdisci, 2024)
School is a very effective place of learning and character-building for students. Education in schools greatly influences knowledge, attitudes, consumption behaviors, and food choices. The Healthy Canteen and School Nutrition Garden are part of health education in schools. Educational institutions must be able to present and provide healthy canteens, as well as healthy food and school nutrition gardens, as one of the services that schools must provide to realize intelligent and healthy children. Therefore, schools are expected to accelerate and innovate food products made based on local food ingredients in schools. This Community Service activity continues NGTS education conducted in 2022 at SMAN 1 Beber. In 2023, we will continue to accelerate and innovate products produced and produced in school gardens and made by school residents for use. In addition, we hope this product innovation can be packaged well with special labeling of SMAN 1 Beber so that it can become one of the school's efforts to commercialize superior products that characterize SMAN 1 Beber.